Identifying factors influencing rezoning in Woldia town of North Wollo, Amhara Region, Ethiopia - Nigatu Amsalu Workineh; Dereje Shitu Shiferaw; Degarege Dagnaw Bogale; Minyichil Teshome Kassahun (Sustainable Futures)
Woldia town has a land-use plan aimed at guiding urban development and addressing challenges. However, the plan's implementation has not effectively tackled the town's real issues, resulting in frequent rezoning, which often reflects a failure to properly execute the plan. The factors behind these rezoning are not well studied, with existing research providing inconsistent findings and failing to identify the primary cause for frequent rezoning requests. Therefore, this study aims to investigate the factors influencing rezoning in Woldia and identify the key drivers behind the frequent requests. A mixed-methods approach, including structured questionnaires and semi-structured interviews with residents, urban planners, and government officials, was employed. Data were analyzed using the Relative Importance Index (RII) and Henry Garrett's ranking technique. The findings reveal that the most significant factor driving rezoning is weak enforcement of existing laws, followed by the misuse of government power, the local government's weak financial capacity, the lack of proper land-use regulations, and financial constraints faced by private developers. These issues hinder the efficient implementation of land-use plans and lead to inconsistent rezoning. The study emphasizes the need for stronger legal frameworks, improved governance, and increased financial resources for urban development. This research contributes to urban planning literature by providing insights into rezoning dynamics in emerging economies. The findings offer valuable policy recommendations, including stronger enforcement mechanisms, financial incentives for sustainable development, and inclusive community engagement in zoning decisions. Addressing these issues is critical to ensuring equitable and sustainable urban growth in Woldia and similar towns.